Conceptual framework of construction professionals' BIM competencies assessment / Seri Nanisa Sima Yusoff, Juliana Brahim and Rumaizah Mohd Nordin - Sima Yusoff, Seri Nanisa; Brahim, Juliana; Mohd Nordin, Rumaizah (College of Built Environment, 2023)
The uncertainty of the current construction professionals' BIM competency level.